WACANA PENANDA KEKOHESIAN DAN KEKOHERENSIAN DALAM BERITA COVID-19 DI LIPUTAN6.COM - Zulfa Nur Maulida (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study analyzes cohesion and coherence in covid-19 news in the June 2020 liputan6.com edition. The purpose of this study is to describe the markers of cohesion and coherence of news discourse in online media with the June 2020 edition of Covid-19. This study aims to describe the discourse markers of cohesion and coherence in the Covid-19 news on the June 2020 edition of Liputan6.com. Looking for markers of cohesion and coherence in the news. Based on the results of data analysis found several things as follows. First, markers of grammatical cohesiveness by using reference markers, substitution, ellipsis, and conjunctions. Second, markers of lexical cohesion which include antonymy, hyponymy, and collocation. Third, the markers of coherence are found as